Relationship between leisure activity and depression in Chinese older adults: chain mediating effect of diet and cognition - Yan Cui; Ying Duan; Jing Du; Ling Yang; Xi Tian; Huaqing Liu (BMC Geriatrics)
Abstract Background Leisure activity was associated with depression in older adults. However, the specific processes by which diet and cognition mediate the role of leisure activities and depression remain uncertain. The study aims to investigate the relationship between leisure activity and depression in older people and the underlying mechanisms involved, while constructing a comprehensive model that links these variables. Methods Data came from the 2018 Chinese Longitudinal Healthy Longevity Survey. Mini-Mental State Examination and CES-D-10 were used to assess cognition and depression, respectively. PROCESS macro was employed to assess the mediation effects of diet and cognition on the relationship between leisure activity and depression. Results Leisure activity was negatively associated with depression, with 35.90% of the total effect mediated through dietary diversity and cognitive function, of which 1.28% was from the chain-mediated effect of dietary diversity and cognition. In addition, 20.94% of the total effect mediated through a plant-based diet and cognitive function, of which 0.43% was from the chain-mediated effect of plant-based diet and cognition. Conclusions Leisure activities are linked to depression, with diet and cognition acting as chain-mediating factors. Public health experts recommend that older adults engage in leisure activities, ensure a broad spectrum of dietary intake, and prioritize the augmentation of plant-based diets as preventative strategies against depression.